The influence of development programs organizational culture and work environment on the quality of human resources at the Peukan Bada Aceh Besar sub-district office employee - Amelia Rahmi; Zuraidah Zuraidah; Said Ashlan (Institute of Computer Science (IOCS), 2023)
This study entitled The Influence of Development Programs, Organizational Culture, and Work Environment on the Quality of Human Resources for Peukan Bada Aceh Besar District Office Employees, aims to determine the extent of the partial and simultaneous influence. Employees of the Peukan Bada Aceh Besar sub-district office made up the study's sample of 30 subjects. A questionnaire or list of questions was used to collect the data for this study. To determine the impact of the independent variable on the dependent variable at the 95% confidence level ( = 0.05), hypothesis testing uses multiple linear regression analysis, F test (simultaneous), and t test (partial). Development program variables affect the quality of human resources, according to the research's partial test results. According to a partial test, the research's findings show that work environment factors, organizational culture factors, and development program factors all have an impact on the quality of human resources for employees. Also, using a simultaneous test, it was discovered that the factors of the Development Program, Organizational Culture, and Work Environment had a favorable impact on the Quality of Human Resources for employees of the Peukan Bada Aceh Besar District Office.